1990
DOI: 10.1177/106002809002400403
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Diclofenac Sodium versus Intravenous Baralgin in the Treatment of Renal Colic

Abstract: A comparative, randomized, double-blind study of diclofenac sodium 75 mg im versus Baralgin (a combination drug composed of dipyrone and two spasmolytics) 5 mL iv was performed on 57 patients with renal colic. Both groups were comparable as to age, sex, pain evolution time before treatment, and no treatment for renal colic in the six hours preceding trial drug administration. No significant differences were found between the two groups with respect to the evolution of pain after the first dose or in the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…In the USA, opioids are the primary means of controlling pain in patients with renal colic. However, since the late 1970s, NSAIDs have been widely used outside the USA to treat renal colic and many studies have confirmed their efficacy [ 20–27]. In a recent meta‐analysis, Labrecque et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, opioids are the primary means of controlling pain in patients with renal colic. However, since the late 1970s, NSAIDs have been widely used outside the USA to treat renal colic and many studies have confirmed their efficacy [ 20–27]. In a recent meta‐analysis, Labrecque et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yılmaz ve arkadaşlarının spontan taş pasajına alfa blokörlerin etkisini değerlendirdiği çalışmasında tamsulosin, terazosin, doxazosin'in üçünün de kontrol grubuna göre istatistiksel olarak taş pasajında önemli etkiye sahip olduğu ve daha az analjezik ilaç gereksinimi duyulduğu, ağrı epizotlarını azalttığı bildirilmiştir 48 . Sanahuja ve arkadaşlarının 57 hastayla yaptığı intramuskuler diklofenak sodyum ile dipyron+spazmolitik birleşimi ilacı karşılaştırdığı çalışmada diklofenak daha etkin bulunmuştur 66 . Lopes ve arkadaşlarının renal kolikte intranazal desmopresin ile intramuskuler diklofenak ve desmopresin+diklofenak ilaç gruplarını karşılaştırdığı çalışmada desmopresin'in diklofenak'ın etkinliğini arttırdığını saptamışlardır 67 .…”
Section: Renal Kolik Tıbbi Tedavisine Yönelik Bazı çAlışmalarunclassified
“…However, 37.5% of patients still experienced moderate or severe pain at 15 minutes. 10 Therefore, an effective and available therapy is urgently needed to accelerate pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Pain alleviation was observed with a mean (SD) of 18.64 (7.99) minutes after intramuscular diclofenac sodium injection. However, 37.5% of patients still experienced moderate or severe pain at 15 minutes . Therefore, an effective and available therapy is urgently needed to accelerate pain relief.…”
Section: Introductionmentioning
confidence: 99%